Evidence for insectivory in Chiropotes satanas - Ayres, José Marcio; Nessimian, Jorge (Primates, 1982)
Chiropotes spp. are normally considered to be entirely herbivorous, specializing in seed predation. However, we report on a single stomach of Chiropotes satanas chiropotes that contained at least 133 insects of at least ten families suggesting the possibility of facultative omnivory. © 1982 Japan Monkey Centre.